Prasmingas švaistymas: žygiai į Prūsiją ir Lietuvą Pierre’o Bourdieu kapitalų teorijos požiūriu - Paravicini, Werner (Lietuvos istorijos studijos, 2011)
Applying Pierre Bourdieu’s theory of capital, the paper examines the reasons why the Western nobleman crusaded to Prussia and Lithuania. The author has detected a huge amount of such marches, especially in the 14th century. In his research, he has applied Bourdieu’s categories in search of what capital was expected to be brought from Lithuania and Prussia—economic, cultural, social, symbolic, or religious (added by the author) one. According to the author, the economic circulation of capital can be used as a model to show (and prove by sources) the circulation of another capital—that of honour, since both were closely connected.